The Kellogg College Centre for Research into Assistive Learning Technologies - McKnight, L; Davies, C (2012)
Purpose: This article aims to introduce the Kellogg College Centre for Research into Assistive Learning Technologies, which is a new research centre based at the University of Oxford. Design/methodology/approach: The article briefly sets the context of the centre within the current literature, and outlines the centre's current plan of work. The centre has funding for two years to look into new developments in the application of digital technologies to support the learning and educational achievement of young people in school and higher education with a range of specific learning difficulties. This will begin with a substantial research review, as well as in-depth studies of current initiatives in secondary schools and higher education. Findings: The findings from the research review will aim to be published and disseminated to the research community within the first two years of the centre's life. Originality/value: It is hoped that this centre will be able to contribute to the existing research on the uses of a range of assistive technologies in educational settings. © Emerald Group Publishing Limited.